STUDI TENTANG PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN TUGAS SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PROTOKOL KESEHATAN PADA MASA NEW NORMAL DI SEKITARAN HOTEL SABRINA PANAM KOTA PEKANBARU - Fernando Fadly; Ahmad Eddison; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Absstract:: Thiis exploration is roused by worries about the course and spread of Coronavirus in packed places and how Satpol PP completes its obligations. The plan of the issue in this study is the means by which is the public view of the execution of the obligations of the common assistance police unit in controlling wellbeing conventions during the new typical period around the Sabrina Panam lodging in Pekanbaru City. The reason for the review was to figure out how the public's view of the execution of the obligations of the common assistance police unit in controlling wellbeing conventions during the new typical period around the Sabrina Panam inn in Pekanbaru City. The advantages of the examination results for understudies are to give an outline of the public impression of the execution of the obligations of the common help police unit in controlling wellbeing conventions during the new typical period around the Sabrina Panam lodging in Pekanbaru City and become a reference for how to act in a public foundation as per the public's view of the execution of the unit's obligations. Common Service Police in controlling wellbeing conventions during the new typical period around the Sabrina Panam Hotel, Pekanbaru City. This examination was directed in Panam in December 2020 - May 2021. This study utilized a quantitative illustrative technique. The populace in this study added up to 194, 331 individuals. The example in this study was taken utilizing the Acidental examining strategy with an enormous number of 100 individuals from the entire local area. So the aftereffects of the estimations got in the above reiteration are 21.8% + 32.8% = 54.6%. In this way, it tends to be presumed that the public's view of the execution of the obligations of the common assistance police unit in controlling wellbeing conventions during the new ordinary time frame around the Sabrina Hotel, attractive sub-area, Pekanbaru City is at the "Good" level.Key Words: Study, Perception, Society, Implementation of Satpol PP, Pandemic.